New species of chiggers (Trombidiformes: Trombiculidae and Leeuwenhoekiidae) from the conservation unit parque nacional da serra das confusões, Brazil - De Castro Jacinavicius, Fernando; Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Horta, Maurício Claudio; Barros-Battesti, Darci Moraes [UNESP] (Oxford University Press (OUP), 2021)
The Piauí State, Brazil, has never had its chigger fauna recorded. In this study, we examined chiggers collected on marsupials, rodents, and lizards from the conservation unit Parque Nacional da Serra das Confusões (PNSC). Herein we describe four new species, Paraguacarus klompenin. sp., Neoschoengastia ochoain. sp., Quadraseta welbournin. sp., and Susa bauchanin. sp. Furthermore, an additional seven species are reported: Eutrombicula alfreddugesi (Oudemans, 1910), Microtrombicula brachytrichiaBrennan, 1971, Microtrombicula rhipidomysiGoff, Whitaker and Dietz, 1983, Parascoschoengastia aemulata (Brennan and Jones, 1964), Parasecia validaBrennan, 1969, Pseudochoengastia petrolinensis Jacinavicius, Bassini-Silva and Barros-Battesti 2019, and Quadraseta flochi (Brennan and Jones, 1960). This is the first report of chiggers in Piauí State, which includes one of the most biodiverse areas in the Caatinga biome and is of particular importance to conservation. The genera Paraguacarus Goff and Whitaker, 1984 and Susa Audy and Nadcharam, 1960 are reported here for the first time to Brazil.
Keywords: Chigger mite; Conservation unit; Ectoparasite; New species